2022
DOI: 10.1111/1365-2435.14187
|View full text |Cite
|
Sign up to set email alerts
|

Do departure and flight route decisions correlate with immune parameters in migratory songbirds?

Abstract: These journeys are energetically demanding and energy reserves of these small birds are limited. Accordingly, most of the time migrating is spent during stopovers that serve to rest, replenish resources and recover. While external influences, like prevailing weather conditions and resource availability, are well studied with regard to stopover behaviour and departure decisions, studies on how birds' individual physiological condition and stopover decisions may be linked are scarce.2. We used a large-scale radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…A potential difference with mainland stopover sites, however, is that the duration of stopovers on Helgoland may be shorter than on the mainland. For example, in the current Helgoland study more than half of the song thrushes departed the night after capture in autumn, whereas at a nearby (German North Sea coastline) mainland stopover site, median autumn stopover duration of song thrushes was 13 days [ 5 ]. Perhaps, some migrants leave Helgoland, as part of a landscape movement within the stopover environment [ 48 ], and fly to the mainland (ca.…”
Section: Discussionmentioning
confidence: 99%
“…A potential difference with mainland stopover sites, however, is that the duration of stopovers on Helgoland may be shorter than on the mainland. For example, in the current Helgoland study more than half of the song thrushes departed the night after capture in autumn, whereas at a nearby (German North Sea coastline) mainland stopover site, median autumn stopover duration of song thrushes was 13 days [ 5 ]. Perhaps, some migrants leave Helgoland, as part of a landscape movement within the stopover environment [ 48 ], and fly to the mainland (ca.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several thrush species show lower total leukocyte counts upon arrival at stopover sites in spring, reflecting such trade‐offs (Owen & Moore, 2008 ). Variation in immune investment may in turn affect departure decisions; recent work demonstrated that songbirds with higher titers of natural antibodies and immunoglobulin Y have longer spring stopovers (Brust et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…atmospheric conditions, along the route [21] and adjust their migratory behaviour according to intrinsic factors, e.g. energy stores [22][23][24] and immune function [25,26]. For example, weather conditions that induce high metabolic costs of migratory endurance flights, such as headwinds, could lead to lower survival [27].…”
Section: Introductionmentioning
confidence: 99%